Charge-patching method for the calculation of electronic structure of polypeptides. Issue 36 (3rd September 2018) - Sun, Chang-Liang; Liu, Li-Ping; Tian, Fubo; Ding, Fu; Wang, Lin-Wang
Abstract : Based on the CPM method, the charge densities of polypeptides can be generated and their electronic structure can be further calculated. Abstract : Theoretical study of the electronic structures of protein is a fundamental challenge in computational biochemistry due to the large size of the systems. The electronic structure of a protein is important for some of the important protein functionalities, such as photosynthesis. In this study, we explored the charge-patching method to calculate the electronic structure of polypeptides. This method generates the charge densities of the systems by patching the charge motifs calculated from small prototype systems. The method was tested on a range of polypeptides, including the glycine polypeptide in 27 -ribbon, α-helix, 310 -helix, and β-strand structures. After the charge density profiles of these systems were obtained, the electronic structures of these glycine polypeptides were further calculated based on density functional theory (DFT) using a folded-spectrum method. The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were analyzed and compared with conventional direct DFT calculations. The charge-patching method results were found to be in good agreement with the directed DFT results.